Emma's strange pet - Little, Jean, 1932-; Plecas, Jennifer ([New York] : HarperCollins, 2003)
Emma is allergic to animals with fur, but because she and her adopted brother really want a pet, they decide to try a lizard.
"3, reading alone.".
Bulletin (Center for Children's books).
Horn Book.
School Library Journal starred.
3.3
3-6
Keywords: Adoption -- Juvenile fiction; Allergy -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Lizards as pets -- Juvenile fiction; Adoption -- Fiction; Allergy -- Fiction; Brothers and sisters -- Fiction; Lizards as pets -- Fiction; Pets -- Fiction; Adoption -- Fiction; Allergy -- Fiction; Lizards as pets -- Fiction; Pets -- Fiction; Siblings -- Fiction; Readers (Elementary).